Respiratory tract barrier dysfunction in viral-bacterial co-infection cases - Tomoko Sumitomo; Shigetada Kawabata (Elsevier, 2024)
A preceding viral infection of the respiratory tract predisposes the host to secondary bacterial pneumonia, known as a major cause of morbidity and mortality. However, the underlying mechanism of the viral-bacterial synergy that leads to disease progression has remained elusive, thus hampering the production of effective prophylactic and therapeutic intervention options. In addition to viral-induced airway epithelial damage, which allows dissemination of bacteria to the lower respiratory tract and increases their invasiveness, dysfunction of immune defense following a viral infection has been implicated as a factor for enhanced susceptibility to secondary bacterial infections. Given the proximity of the oral cavity to the respiratory tract, where viruses enter and replicate, it is also well-established that oral health status can significantly influence the initiation, progression, and pathology of respiratory viral infections. This review was conducted to focus on the dysfunction of the respiratory barrier, which plays a crucial role in providing physical and secretory barriers as well as immune defense in the context of viral-bacterial synergy. Greater understanding of barrier response to viral-bacterial co-infections, will ultimately lead to development of effective, broad-spectrum therapeutic approaches for prevention of enhanced susceptibility to these pathogens.